1.0k views
0 votes
Solve h2-42 = -h using the quadratic formula.

A) h = 0 or h = 7
B) h = -6 or h = 7
C) h = 6 or h= -7
D) h = -6 or h = -7​

1 Answer

3 votes

Answer: Option C

h = 6 or h= -7

Explanation:

We have the expression


h^2-42 = -h

To solve add h on both sides of the equality


h^2+h-42 = -h+h


h^2+h-42 = 0

For an equation of the form
ah^2 +bh +c the quadratic formula is


h=(-b \± √(b^2 -4ac))/(2a)

In this case


a = 1\\b= 1\\c =-42


h=(-1 \± √(1^2 -4(1)(-42)))/(2(1))


h_1=6


h_2=-7

The answer is the option C

User Craig Squire
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.